Indirect Assessment of Outcomes in Education: A-Review - Bhatia, J; Singh, H (International Journal of Computer Sciences and Engineering, 2025)
Outcome Based Education (OBE) is the focal point of teaching and learning methodology. To achieve OBE many components are essential like Programme Educational Objectives (PEOs), Exit Outcomes (EOs), Programme Outcomes (POs), Course Outcomes (COs), Graduate Attributes, Lesson Outcomes, Unit Outcomes, Vision and Mission. Attainment of any of these components lead to the achievement of OBE and validate the teaching- learning process. Modes of Outcome Based Assessment can be direct (tests, assignments, projects, end examinations, formatives) as well as indirect (feedback, discussion forums, blogs). Much work has been done to check the attainment of outcomes and achievement of OBE using the direct assessment tools. This study focuses on the development of a systematic approach to check the achievement of OBE using automated indirect assessment tool. Traditional way of assessing the attainment of outcomes is not optimal. As to manually calculate the attainment from the huge datasets requires much effort. Hence, automated process of indirect assessment of outcomes has become the necessity in today’s era.